Sehay pot’i Sateré-Mawé: a educação no “Espaço de Estudo da Língua Materna e Conhecimentos Tradicionais Indígenas Nusoken I” - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
The research, entitled "Sehaypóri Sateré - Mawé: education in the 'Space for the Study of Mother Tongue and Traditional Indigenous Knowledge - Nusoken I'", analyzed the historical, legal and conceptual interfaces from which the educational policy for the Sateré-Mawé people of the Nusoken Space in the municipality of Manaus is constituted. The Space is located in the Redenção neighborhood, west-central zone of the urban area of Manaus. It has the perspective of working with bilingual education, aiming at the transmission of traditional knowledge, based on the affirmation, valorization and strengthening of the mother tongue and cultural identity. This study seeks to answer the following question: how are the historical, legal and conceptual interfaces of the educational policy of the Nusoken Indigenous Mother Tongue and Traditional Knowledge Study Space constituted? The categories of analysis, Indigenous Education, Indigenous School Education, and Democratization, serve as support, because they are aligned with the research objectives, and are worked on theoretically by the chosen authors, fomenting the analysis of the research with the concepts that discuss elements for a differentiated education. Methodologically, the study is anchored in a qualitative theoretical perspective, from bibliographic and documentary research, based on the historical-materialist approach. Legal landmarks were selected (CF 1.988, CNE/CEB Res. 05/2012, CNE/CEB Parecer13/2012), articles (BRITO KAIAPÓ,2019; SERPA & GRANDO,2018), books, (MELIÀ, 1979; GONZAGA, 2021), dissertation (SANTOS, 2012), which brought information about the existence and effectiveness of the educational policy for indigenous school education in governmental spheres. Finally, we worked with the analysis of the legal documents of the Municipality of Manaus (Decree 1.394/2011 and Law 2.781/2021) that are the basis for Indigenous School Education in Manaus and for the Spaces for the Study of the Mother Tongue and Indigenous Traditional Knowledge. As results, we identified elements that indicate that the indigenous peoples living in the urban area of the municipality of Manaus had many of their demands incorporated into public policy due to the struggles of movements, organizations and leaderships, especially after 2011, but that the Knowledge Spaces did not follow the same movement, presenting difficulties that extend from the field of meaning, integration and association with the policy for indigenous school education, as the space of a people present in the urban environment. The data indicate that the Space for the Study of the Mother Tongue and Traditional Indigenous Knowledge Nusoken I has become a Network of Influences in the urban territory of the Municipality of Manaus, through its cultural activities open to the public and by receiving the community around it. The Nusoken I Space manages to work with Indigenous School Education, despite being an annexed room and not being in the category of indigenous school, it reaches its objectives, however, it is necessary that the State reevaluates the legislation in order to fulfill some of the desires and current needs that the Space requires. In this way, the Space is consolidated because it resists, as an environment for sharing knowledge so that the children who study there realize the strength and importance of knowing their ancestry and the essence of their people, because even in urban territory the identity of the Sateré - Mawé people remains and is reinforced.

Motpap kat hap, Sehay pot’i Sateré-Mawé etiat, Wemu’e hap “Wemu’e aipusu etiat hawyi Aha’awyria Tapy’yiaria Mikuap ko’i Mienoi etiat – Nusoken I”. Toikat’i-kat’i sehay nimuat wakuat hawyi irania’in wemu’e mesuwat akagnia irania’in minug wemu’e hamuat Sateré-Mawé ko’i piat wemu’e hap Nusuken piat, Manaus totiat. Wemu’e hap toigne’en Redenção note, tawa Manaus py’asetpe, motpap, typy sehay etiat wepu’e hap, i’ewyte nimuaria mikuap porerekosap hap ko’i etiat, sat’i-sat’i hawyi musu muesaika hawyi seko ko’i etial. Mesuwat wemu’e hap ti ikat mewat apo’e hap ko’i etiat: Aikota asom toine’en meimewat sehay nimuat wakuat ko’i hawyi irania’in wemu’e hap ko’i potpap, Wemu’e aipusu etiat hawyi Aha’awyria Tapy’yiaria Mikuap ko’i Mienoi etiat Nusoken note? Mesuwat wemue’e hap tapy’yia wemu’e hap upiat pote, akagnia, wemu’e hap akag ko’i kaipyi asom toig mowyro hap mejuwat mienoi het rakat rote? Tapy’yia wo’opotmu’e hap, Tapy’yia mu’e hap hawyi akagnia miporerekosap asom waku mowyro hamo? katpote ti mi’iria tukupte’en mesuwat motpat kat hap ko’i minug wuat ko’i pe, mi’iria ti mimoherep iwan muapyi yn, mi’airo iwan haria ko’i kaipyi, mimoherep mikat’i-kat’i kapyi mesuwat wemu’e tuwa’awywuat motpap puapyi hamo. Wo’omu’e hap puapyi pote, wemu’e hap tuwepytyk miwan herewiat, mikat’i-kat’i kaipyi hawyi miwan mienoi kaipywiat, mewat miwan nimuat ko’i kaipyi. Mi’atunug ko’i ti menti pywo piat ehap (CF 1.988. CNE/CEB Res. 05/2012. CNE/CEB Hewaku hap 13/2012), Saikap moherep hap ko’i, (BRITO KAIAPÓ, 2019; SERPA e GRANDO, 2018), Popera (MELIÀ, 1979; GONZAGA, 2021), miwan (SANTOS, 2012), meigmewaria ti herut imoherep mesuwe toine’en hawyi imoheg mo’opotmu’e kuap hap tapy’yiaria piat hamuat torania mesuwat akagnia potpap hap upi. Ikahuro hamo ti, urupotpap mesuwat iwan saikap Manaus piat wywo (Mo’oro hap 1.394/2011 hawyi saikap 2.781/2021), meime ti tapy’yiaria wo’opotmu’e hamuat hap etiat Manaus piat hawyi i’ewyte Wemu’e aipusu etiat hawyi Aha’awyria Tapy’yiaria Mikuap ko’i Mienoi etiat hap ko’i totiat wo’opotmu’e hamuat. Imoma hamuat ko’i wo ti, uruipuenti mesuwe tapy’yiaria gupte’en Manaus totiaria weigne’en haria tukup’en akagnia pope rakaria ewy mekewat wo’omuesaika hap ko’i upiat, wa’atunug hap hawyi tu’isaria potpap upi mi’i ti 2011 pyi ra’yn, ma’ato wemu’e hap meigmewat musu etiat wo’omu’e hat yt tuwemoherep’i meimewat motpap mi’i nug hamo mi’i ti motpap pyhyp takat ewy, wa’atunug hap hawyi wo’atunug saikap wuat wemu’e hap wywo, aikota tukupte’en mit’in tawa wato py’asetpe pykai. Mesuwat timoherep ti mejuwat Wemu’e aipusu etiat hawyi Aha’awyria Tapy’yiaria Mikuap ko’i Mienoi etiat – Nusoken I, ti wo’omogku’ura’i hap mo toine’en Manaus pe meimuewat topotpap seko ko’i moherep torania mit ‘in piat hap upi hawyi irani’in gupte’en ta’atuete’i rakaria ewaku hap upi. Wemu’e hap Nusuken I ti ipotpap kuap aikota waku watopotmu’e tapy’yiaria mu’e hap ewy, wemu’e hap pepak pe pykai yt wemu’e hap sese ite pykay, toipuenti tomikat ko’i, mi’i tupono ti mejuwat wemu’e hap tikat kuap meigmewat saikap ko’i pua toipuenti po’og saikap tomikyesat piat hamo hawyi aikowat mik’yesat po’og mejuwat wemu’e hawiat. M’i tupono mejuwat wemu’e hap toine’en hesaika rakat wo katpote toine’en iheg nakat no, katupono mejuwat toine’en guap ko’i ahyt porerokosap hap ko’i hirokaria wemu’e haria tikuap kuap saika hap hwyi i’ewyte kat hamo waku ta’atukuap ta’atusa’awy hawyi ta’atuekaria-karia’i Sateré-Mawé ywania wat.
Sehaypóri Sateré – Mawé: education in the "Space for the Study of Traditional Mother Tongue and Knowledge Indigenous Nusoken I"
Sehay pot’i Sateré-Mawé: Wemu’e hap “Wemu’e aipusu etiat hawyi Aha’awyria Tapy’yiaria Mikuap ko’i Mienoi etiat – Nusoken I”
Keywords: Indígenas - Educação; Mawé (Povo indígena) - Educação; Escolas indígenas - Manaus (AM); Educação multicultural; CIENCIAS HUMANAS: EDUCACAO; Educação indígena; Comunidade Waikiru I; Espaço Nusoken; Políticas educacionais; Indigenous Education; Community Waikiru I; Nusoken Space; Educational policies; Tapy’yia wo’omu’e hap; Tawa Waikiru I; Wemu’e hap Nusoken; Akagnia wo’omu’e hap upiat